(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: This study aimed to describe the clinical characteristics of pneumoconiosis in a coal processing company. Methods: A cross-sectional was conducted on 805 workers at the Coal and Port Joint Stock Company, Quang Ninh Province from January 2019 to October 2020. Results: 23.4% of pneumoconiosis patients experienced shortness of breath; 39.2% had a cough, and 8.9% had chest pain. Shortness of breath typically occurred during exertion, each episode of cough lasting about 2 weeks, and chest pain usually occurred in the back near the shoulder blades. Conclusion: Pneumoconiosis often presents with poor and late clinical characteristics, making it essential for workers exposed to coal dust to undergo regular occupational health check-ups to detect pneumoconiosis early.